Gender-specific association of oxidative balance score with sarcopenia in American adults: NHANES 2011–2018 - Xinyi Pei; Di Jin; Lin Liu; Qingrao Song; Da Pan; Baofu Guo; Wei Xie (Experimental Gerontology)
Background & aims: Nutritional status and levels of oxidative stress may be modifiable risk factors for the development of sarcopenia. The Oxidative Balance Score (OBS) is a comprehensive measure of oxidative balance in diet and life exposures. We conducted a cross-sectional study to investigate the association between OBS and sarcopenia in US adults. Methods: Based on the 2011–2018 National Health and Nutrition Examination Survey (NHANES), this study included 3084 participants. Weighted logistic regression analysis and restricted cubic spline regression (RCS) were used to assess the association between OBS and sarcopenia, as well as gender differences in this association. Results: OBS and sarcopenia are negatively associated (OR = 0.951, 0.919–0.983, p = 0.004). Compared with the lowest quartile of OBS, the highest quartile was significantly negatively associated with sarcopenia (OR = 0.431, 0.202–0.917, p for trend = 0.01). Both dietary OBS and lifestyle OBS were significantly negatively associated with sarcopenia (OR = 0.963, 0.930–0.997, p = 0.032; OR = 0.634, 0.562–0.715, p < 0.001). In gender subgroup analysis, a significant negative association between OBS and sarcopenia was observed in women (OR = 0.916, 0.862–0.973, p = 0.005), while the association was not significant in men. The RCS showed a significant linear correlation between total population OBS, female OBS and sarcopenia (p for nonlinear >0.05, p for overall <0.05). Conclusions: Higher oxidative balance scores are associated with a lower prevalence of sarcopenia, particularly among women. These findings support the importance of antioxidant-rich diets and healthy lifestyles in mitigating sarcopenia risk, especially in aging female populations.